Advanced Perl programming : from advanced to expert - Rothwell, William (Apress L.P., 2020)
William Rothwell's Advanced Perl Programming continues where his previous book left off, more or less, as it guides you through advanced techniques of the Perl programming language starting with command-line options, references, and arrays and hashes from advanced data types. Next, you'll learn about typeglobs for symbolic entries. Additionally, you'll see advanced subroutine handling, then packages and namespaces. Furthermore, you'll build advanced modules and install CPAN modules. Unlike Java and C++, modules have been around in Perl for a long time now. Along the way, you'll learn and use POD mark up language for Perl documentation. Moreover, you'll get a survey of the many advanced features and data structures of the current Perl programming language. You'll also get a survey of the new features of the latest Perl 5.x release. After reading and using this book, you'll have the tools, techniques, and source code to be an expert Perl programmer. You will: Carry out command-line parsing and extract scripts Create references; return values from a reference; work with the ref Function and strict refs Work with advanced Perl data types using arrays, hashes, and hash of hashes Use Typeglobs for symbol table entries Build modules and install CPAN modules Write documentation for Perl using POD Work with the newest features in Perl, including the smartmatch operator, yada yada, automated regex modifiers, the CORE namespace and more.